Chambers dictionary of phrasal verbs (Chambers Harrap, 1996)
The book offers over 3.000 phrasal verbs used in English today, thousands of synonyms and and antonyms, thousands of examples of phrasal verbs in use in everyday English from the authotative British National Corpus, examples of new phrasal verbs from Chambers Wordtrack; full-sentence definitions place the phrasal verbs in their correct grammatical and collocational contexts